Board Communities in Formation of Qanun Regional in Aceh Parliament - S. Amirulkamar; Ismail (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
The Government system of the Unitary State of the Republic of Indonesia according to the 1945 Constitution of the Republic of Indonesia recognizes and respects special or special regional government units (Special in the Religious Field, Special in the Field of Education and Special in the Customary Field) regulated by Constitution. In this case the Regional People's Representative Council (DPRD), which is abbreviated as DPRD, but names Aceh as a Provincial Region in the Unitary State of the Republic of Indonesia system based on the 1945 Constitution of the Republic of Indonesia and the title of elected government official will be determined by the DPRA after the 2009 general election. This is only a change in the legal nomenclature with the status remains in the position of Aceh Privileges. This long journey is the existence of the Council community in the formation of the Regional Qanun in the Aceh Parliament in the form of a legislative body as one of the tools of the DPRA that manages the formation of the Regional Qanun which is carried out jointly with the Regional Head. This is done with the delegation of government authority to the Regional Regions as a political tool in the struggle for human rights and the rights of social aspirations, as well as the Aceh People's Representative Council or the Aceh DPR as a nomenclature of legislative institutions in regions that have legitimated importance in governance. The regulation of laws and regulations in Indonesia as a constitutional basis for the 1945 Constitution of the Unitary State of the Republic of Indonesia article 18B paragraph (1) states that "the State recognizes and respects special or special regional government units that are regulated by laws invite.